KITAB KUNING DAN KITAB SUCI: PENGARUH AL-JABIRI TERHADAP PEMIKIRAN KEAGAMAAN DI NU DAN MUHAMMADIYAH - Ahmad Najib Burhani (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2015)
This article aims to answer the following questions: First, why did the study of al-Jabiris ideas so fertile in Nahdlatul Ulama (NU), especially among the post-traditionalist group, while in Muhammadiyah, including the progressive group, this did not receive a similar response? Second, how did the post-traditionalist group of NU read and interpret al-Jabiris ideas and implement them in the context of the organization (NU), in particular, and Indonesia, in general. This article shows that: 1) the difference between NU and Muhammadiyah in their treatment and appreciation to al-Jabiri mostly stems from the religious tradition in these two organizations. NUs tradition is strongly influenced by kitab kuning, while Muhammadiyahs tradition is strongly influenced by kitab suci (holy book). 2) The study of al-Jabiris ideas encourages critical thought and discourse within NU, particularly when these ideas were used as a tool to read established doctrines, e.g. the sunni doctrine, and to read the involvement of NU in the 1965 massacre.Keywords: Post-traditionalism, modernism, a??la (authenticity), a?r al-tadw?n (era of codification), tur?th (heritage), tradition, nah?a (renaissance).